The Information Technology Application Change Trend: Its Implications for the Construction Industry - Zainon, Nurshuhada; Rahim, Faizul A.; Salleh, Hafez (Journal of Surveying, Construction and Property, 2011)
As technologies change rapidly, improved information technology (IT) products and services are released every day throughout the world. This phenomenon gives tremendous pressure on construction managers to plan, implement and adopt new technology solution in accommodating such changes. However, looking at the tools that can be used to help in this situation, the understanding of the trends of IT change and its impact to the construction industry is essential. Even though most studies in IT change trend have been carried out across industries; however far too little attention has been paid to measure the trend of IT change in construction industry and how fast it has been invented. The purpose of this paper is to explain the implications of IT change and consequently provides an understanding on how IT is changing in construction industry, its current trends, and what are the predictions of its scenario in future construction industry. The study is based on textual reading ranging from 1996 to the first part of 2011, which was gathered from journals, literature books, specialized databases and other information sources available on the Internet. A principal finding is that even though the introduction of new technology in construction is slower than other industries, the implications towards construction industry have significant impacts. This finding provides useful information in order to develop a tool for construction organizations handling the rapid changes by tackling the issues affected by the IT change. Keywords: IT changes, IT trends, IT investment, construction industry, information technology.